Integrated Approaches for the Management of Rice Root-knot Nematode, Meloidogyne graminicola in Rice (Indian Journal of Nematology, 2024)
The experiments were carried out in the lab, screen-house and field to manage rice root-knot nematode, Meloidogyne graminicola, in rice. In lab assays, rhizobacterial strains and phytotherapeutic substances caused mortality of M. graminicola juveniles at all dilutions, i.e., 1:5, 1:10, 1:20, 1:40 and 1:80 at 1, 2, 4, 6 and 8 days. Among the rhizobacterial strains and plant extracts, the maximum juvenile mortality was observed in Azotobacter chroococcum HT 54 (65.2%), which was at par with the aqueous extracts of Azadirachta indica (61.8%). In nursery treatments in pots, seed treatment with A. chroococcum HT 54 and application of neem cake @ 50 g/pot showed a high biocontrol efficacy against M. graminicola, promoted plant growth of rice and significantly suppressed finalnematode population (147 J2/200 cc soil) as compared to untreated check (923 J2/200 cc soil). In the main field experiment, maximum plant height (124.7 cm) and grain yield (51.2 q/ha) were recorded in the treatments where two deep summer ploughings (10-day interval) and seedlings treated with A. chroococcum HT 54 + neem cake @ 50 g/pot was given. Combination of the treated nursery (A. chroococcum HT 54 + neem cake @ 50 g/pot) with deep summer ploughing significantly reduced the number of galls (29.6), no.of eggs per plant (3551) and final nematode population (138 J2/200 cc soil).